The effect of adjuvant chemotherapy on survival and recurrence after curative rectal cancer surgery in patients who are histologically node negative after neoadjuvant chemoradiotherapy. (1st November 2017) - Baird, D. L. H.; Denost, Q.; Simillis, C.; Pellino, G.; Rasheed, S.; Kontovounisios, C.; Tekkis, P. P.; Rullier, E.
Abstract: Aim: The aim of this study was to evaluate whether adjuvant chemotherapy will affect recurrence rate or disease‐free and overall survival in patients with rectal adenocarcinoma who were staged with MRI node‐positive disease (mrN+) preoperatively. These patients underwent neoadjuvant chemoradiotherapy with curative rectal cancer surgery and their pathological staging was negative for nodal disease (ypN0). There is no consensus on the role of adjuvant chemotherapy in such patients. Method: Patients who received neoadjuvant chemoradiotherapy and underwent curative rectal cancer surgery for rectal adenocarcinoma staged as [mrTxN+M0] on MRI staging and who on pathological staging were found to be [ypTxN0M0] were retrospectively identified from January 2008 December 2012 from two tertiary referral centres (Royal Marsden Hospital, London and Saint‐Andre Hospital, Bordeaux). Results: One hundred and sixty‐three patients were recruited and, after propensity matching at a ratio of 2:1, n = 80 patients were divided to receive adjuvant ( n = 28) or no adjuvant treatment ( n = 52). A comparison of adjuvant chemotherapy vs no adjuvant therapy showed that the mean overall survival was 2.67 vs 3.60 years ( P = 0.42) and disease‐free survival was 2.27 vs 3.32 years ( P = 0.14). Conclusion: This study found no significant difference in survival or disease recurrence between patients who received adjuvant chemotherapy and patients who did not. There is no clear evidence to support or dismiss the use of adjuvant chemotherapy for patients who were node positive on preoperative MRI and node negative on histopathological staging. Further multicentre prospective randomized trials are needed to identify the appropriate treatment regime for this group of patients.